PERENCANAAN PENGELOLAAN PENDAPATAN ASLI DAERAH SEKTOR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DI KABUPATEN BLORA - Nugrahadi, Robi; Sarwono, Sarwono; Riyanto, Riyanto (Department of Public Administration, Universitas Negeri Surabaya, 2018)
This research background is property tax management authority transfer by center government to local government according to the laws of local tax number 28 in 2009. The purpose is to make government financial independently and increase local revenue in property tax sector. Problem of that condition is local government must be set up many supporting factors, that is human resources especially property appraisal, computer and server tools, operating system and data base, compatibel files and service room, and exist budget to implement intensification and extensification tax program. Readiness of supporting factors are very influence optimization level of property tax revenue. According that condition, this research purpose is to analyse property tax management in Blora Regency so that from result of analysing can be arrange scenario planning which is consider uncertainty situation in future. Collecting data method of this research use Miles, Huberman, and Saldana method (2014), while scenario planning analysis use TAIDA method from Lindgren and Bandhold (2003). Result of this research is Government of Blora Regency has not maximaly implement property tax management yet. That condition based on empirical fact which is only one man appraisal to analyse NJOP with more than 500 thousand property tax object in Blora Regency. That situation cause property tax revenue not accordance with real potension.